Zróżnicowanie w poziomie rozwoju województw w Polsce - Gorzałczyńska-Koczkodaj, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The political changes which started in 1989 in Poland affected the economic and social situation. These changes had a direct impact on the competitive position and growth of province. This paper describes general situation of provinces, especially the cities, which are the strongest part of the province. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 233-241